2016
DOI: 10.5539/jas.v8n3p78
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Acid Phosphatases in Ectomycorrhizal Fungi

Abstract: The colonization of plant roots by mycorrhizal fungi, generally increases P content in the host plant when in soils with low levels of P. The objective of this work was to evaluate the activity of acid phosphatases in two isolates of Pisolithus microcarpus, grown in different sources and concentrations of phosphate and to characterize the phosphatase isoenzymes produced by isolates. Both isolates were grown on Melin-Norkrans modified (MNM) medium enriched with organic (Po) or inorganic (Pi) sources of phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Moreover, bacteria associated with extraradical AM hyphae can also secrete phosphatases (Sato et al., 2015, 2019) and phytase secretion has also been associated with extraradical AM hyphae (Wang, Hoffland, et al., 2017; Wang, Shi, et al., 2017). Phosphatase release has been commonly observed in AM and EM (Araujo Costa et al., 2016; Hirano et al., 2022; Joner & Johanson, 2000; Meeds et al., 2021; Qi et al., 2022).…”
Section: Consistent Role Of Mycorrhizas and Root Exudates In Phosphor...mentioning
confidence: 99%
“…Moreover, bacteria associated with extraradical AM hyphae can also secrete phosphatases (Sato et al., 2015, 2019) and phytase secretion has also been associated with extraradical AM hyphae (Wang, Hoffland, et al., 2017; Wang, Shi, et al., 2017). Phosphatase release has been commonly observed in AM and EM (Araujo Costa et al., 2016; Hirano et al., 2022; Joner & Johanson, 2000; Meeds et al., 2021; Qi et al., 2022).…”
Section: Consistent Role Of Mycorrhizas and Root Exudates In Phosphor...mentioning
confidence: 99%
“…[21][22][23] Mycorrhizal mycelia have the capacity to release acid phosphatase, irrespective of available organic phosphorus (P) in the growing substrate, with general specificity to soil habitats pH. 23,24 Li et al 25 , however, found low substrate P to induce higher acid phosphatase activity, whereas Costa et al 24 found organic phosphate to suppress synthesis of acid phosphatase in Pisolithus microcarpus, making it necessary to examine suitable media pH for tropical MMs. In particular, pH was found to regulate extracellular proteases to release nitrogen (N) in amino acids for Amanita muscaria, an MM associated with pine, 20 making it necessary to find the right pH when developing culture media for tropical/subtropical MMs.…”
Section: Introductionmentioning
confidence: 99%